Biculturals, team facilitation and multicultural team performance: an information-processing perspective - Engelhard, Franziska; Holtbrügge, Dirk (European Journal of Cross-Cultural Competence and Management, 2017)
The literature on multicultural teams shows that the characteristics of its members are highly relevant for team performance. However, few studies focus on the influence of culture on supporting processes such as boundaryspanning activities. In this study, we test the impact of bicultural individuals on team facilitation activities and the relationship of these activities with team performance. Based on an information-processing theory, six research hypotheses are developed and tested using a sample of 137 bicultural and monocultural individuals. Partial least-squares (PLS) modelling reveals a significant positive association between biculturalism and team facilitating activities. The study also reveals a mediating effect of internal group processes and group cohesion on the relationship between team facilitation and team performance. An important managerial implication of this study is to consider selecting bicultural individuals when staffing multicultural teams. This is followed by further implications and limitations of the study.The literature on multicultural teams shows that the characteristics of its members are highly relevant for team performance. However, few studies focus on the influence of culture on supporting processes such as boundary spanning activities. In this study, we test the impact of bicultural individuals on team facilitation activities and the relationship of these activities with team performance. Based on an information-processing theory, six research hypotheses are developed and tested using a sample of 137 bicultural and monocultural individuals. Partial least-squares (PLS) modeling reveals a significant positive association between biculturalism and team facilitating activities. The study also reveals a mediating effect of internal group processes and group cohesion on the relationship between team facilitation and team performance. An important managerial implication of this study is to consider selecting bicultural individuals when staffing multicultural teams. This is followed by further implications and limitations of the study.
Keywords: biculturals; boundary spanning; information-processing theory; multicultural teams; team facilitation; team performance